The Role Of Class Teachers In Learning During Covid-19 Pandemic At Sdn Jatiduwur Kesamben Jombang - Mei Kalimatusyaro; Faridatul Umah (JOSSE: Journal of Social Science and Economics, 2022)
Quality in the world of education including the educator or teacher. Thus, educators are required to understand that each student has a different way of learning from one another in physical aspects, thinking patterns, how to respond or learn something new. So, educators must be active in directing students to continue to be motivated in learning. Due to the Covid-19 pandemic, the government enforces online and offline learning for students to study from home or study in groups with a schedule set by each class teacher. Because of this, the teacher's role is very important in increasing student learning motivation, especially all activities related to academics are carried out online. The impact of Covid-19 is not only a challenge in life but the impact of Covid-19 is also a challenge in the world of education. What are the media used by classroom teachers in the learning process during the COVID-19 pandemic, How is the process of implementing learning during the COVID-19 pandemic, starting from planning, implementing and evaluating. as well as what are the obstacles for classroom teachers in learning during the covid-19 pandemic. Thus, this study aims to determine the role of classroom teachers in learning during the COVID-19 pandemic at SDN Jatiduwur, Kesamben, Jombang. Furthermore, from the results of the study, it was written that the learning media used was using an online system through WhatsApp groups. The process of implementing learning during the COVID-19 pandemic, teachers use mixed learning.The learning constraints during the COVID-19 pandemic are the lack of maximum student involvement in learning activities, the involvement of students in online learning is not as big as direct or face-to-face learning, the availability of facilities in online learning, namely Smartphones/Mobile phones, Internet networks are also an obstacle in learning. learning,, The role of parents in learning in online learning during the Covid-19 pandemic, parents find it difficult to accompany students' learning because some parents are workers, some of them are less able to operate smartphones / cellphones.